PENERAPAN TEKNIK SELF-INSTRUCTION DALAM LAYANAN KONSELING KELOMPOK UNTUK MEREDUKSI PROKRASTINASI AKADEMIK SISWA KELAS X SMAN 1 MARGAASIH - Khoerun Nisa, Silmi; Samsudin, Asep; Nurul Fauzia, Azni (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
The research conducted in class The biggest triggers are caused by stress and anxiety so that students prefer to do activitiesthat are more enjoyable than completing the demands of school work. Furthermore, self-instruction techniques in group counseling to reduce academic procrastination have proven to be effective. This research uses mixed methods with an explanatory sequential design. The research results show that students are more involved in the learning process, understandthe process better, and have alternative ways to solve problems. Data analysis including pretest and posttest data showed that eight members of the experimental group experienced significant changes after receiving the service. The pretest results show a score of 82.2% and a posttest score of 72.7%, so the self-instruction technique in the form of self-verbalization ingroup counseling is effective in reducing students' academic procrastination. Another finding in this research is that teachers need to understand that procrastination is not just a matter of laziness, but can be caused by various factors such as anxiety, inability to manage time, or lack of motivation. By understanding students' conditions empathetically, teachers can deal withthis problem better, create a regular schedule to monitor student progress, provide encouragement, provide constructivefeedback, and offer strategies to overcome procrastination.